What’s charisma got to do with it? Three faces of charismatic leadership and corporate social responsibility engagement - Hu, Jinyu; Dutta, Tanurima (Frontiers in Psychology, 2022)
In response to both internal and external expectations and pressures, companies increasingly consider corporate social responsibility (CSR) as an essential factor in their strategic planning, but in a very diverse manner. To help synthesize the flourishing research in CSR variation across firms, we propose a three-orientation framework to map out a wide range of CSR strategies in current literature. Furthermore, we emphasize the importance of executive leadership and suggest that differences in leader’s values are the key drivers of CSR heterogeneity. This study offers a parsimonious model that maps out three primary pathways between leadership values and CSR strategic configurations. Drawing from charismatic leadership theory, we argue that three distinct types of leader power motives define three modes of leader’s strategic decision frames, which in turn influence corresponding CSR orientations. Specifically, socialized charismatic leaders favor prosocial decision frame that results in integrative CSR orientation; neutralized charismatic leaders embrace instrumental decision frame leading to strategic CSR mode; and personalized charismatic leaders tend to adopt self-serving CSR strategies driven by the self-serving decision frame. This holistic view advances the knowledge about the micro-foundations of CSR drivers and the essential role of leader values.